Relationship between Neonatal Skin Bilirubin Level and Severe Jaundice with Maternal, Childbirth, and Neonatal Characteristics - Mojgan Mirghafourvand; Robabe Seyedi; Abdollah Jannat Dost; Sakineh Mohammad-Al; Mohammad Asghari Jafarabadi (Mashhad University of Medical Sciences, 2019)
Background: Neonatal jaundice is the most common cause of newborns' hospitalization. This study aimed to examine various maternal, childbirth, and neonatal factors affecting the neonatal skin bilirubin level and severe jaundice. Methods: This cross-sectional study was conducted on 1066 healthy neonates with a gestational age of 35 weeks or over and birth weight of ≥2000 g at teaching hospitals of Alzahra and Taleghani in Tabriz, Iran, during 2016-2017. The participants were selected using convenience sampling. Data were collected using a three-part researcher-made questionnaire assessing maternal, childbirth, and neonatal characteristics based on the medical histories of mothers and newborns as well as interviews with mothers. Neonatal jaundice was measured utilizing the Kj-8000 device on days 3-6 after birth by measuring the skin bilirubin level. Moreover, the need to phototherapy (severe jaundice) was determined based on the American Academy of Pediatrics guideline. The generalized linear model and multivariate logistic regression were employed for data analysis. Results: Out of the followed-up neonates, 94 (9.96%) cases developed severe jaundice and 850 (90.04%) newborns did not show any symptoms of this complication. The results of the adjusted generalized linear model showed that infant's bilirubin level correlated significantly with a history of jaundice in previous children, infant's age at first meconium excretion, frequency of feeding, gestational age, mother's blood type, and a number of maternal ultrasound during pregnancy. Moreover, the results of adjusted logistic regression revealed an association between severe jaundice and variables, such as the place of residence, history of jaundice in previous children, feeding the infant with water or sugar water during breastfeeding intervals, frequency of feeding the infant, gestational age, mother's blood type, time of discharge from the hospital, and number of pregnancies. Conclusion: Some factors related to neonatal jaundice were identified to raise the awareness of healthcare personnel for the early identification and treatment of neonatal jaundice in order to prevent its complications.